PORTUGUESE CIVIL WAR REFLECTED BY ALBINA ROMÂNEASCĂ / ROMANIAN BEE IN 1832 - Marinescu, Luiza (POLISSEMA – Revista de Letras do ISCAP, 2014)
The paper referring to the year 1832 in Portugal reflected in the literary reportage of war from the one of the first Romanian newspapers “Albina românească” (“Romanian Bee” translated title) edited by Gheorghe Asachi illustrates the idea that the first reportages describing the war from Romanian literature differ from strict journalistic reports by the following elements: the artistic vision and the aesthetic message. This paper starts the investigation and the selection of the newspaper reportages about Portugal’s civil war belonging to the archive of 1832 first Romanian newspaper called “Albina românească” edited by Gheorghe Asachi to illustrate different aspects about the foundation or invention of a new literary genre, one of the species of the literary journalism with a long tradition in Romanian press: the reportage about war. Disseminated through the first Romanian newspaper 182 years ago, the reportages about Portuguese civil war are grouped together to outline the following aspects: 1. Gheorghe Asachi and his vocation of founder; 2. “Albina românească”(1829): the first Romanian publication with a long occurrence; 3. The Reportage about War: Definition and Features; 4. The Artistic Vision and the Aesthetic Message of the Romanian Literary Reportage about Portugal’s Civil War in “Albina românească” from 1832; 5. Conclusions.